Analisis Mikrobiologi Dengke Naniura Ikan Mas (Cyprinus carpio L) Terhadap Pengaruh Konsentrasi Andaliman (Zanthoxylum acanthopodium DC) - fadhliani; Yesika Rumondang Sitorus; Zidni Ilman Navia (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
Dengke naniura is a traditional fermented food made from carp which is often consumed in the traditional ceremonies of the Batak people. This study aims to determine the effect of the concentration of andaliman (Zanthoxylum acanthopodium DC) the best concentration of andaliman (Zanthoxylum acanthopodium DC) on microbes in dengke naniura. The method used in this research is an experimental method. The experimental design that will be used is a non-factorial Completely Randomized Design (CRD), with 4 variations of andaliman concentrations of 0 g (A0), 25 g (A1), 27.5 g (A2), 30 ( A3). Dengke naniura’s microbial testing was carried out at the Samudra University Laboratory. The best concentration after addition andaliman to the microbial colonies that appeared after incubation was at the A3 (30 g) concentration. The number of microbes that can be counted on the addition 30 g andaliman is 3.66 x 104 colonies/g had met the standardization of SNI for food maximum 5.0 x 105 colonies/g.